Respostas do Gastrópode Littoraria angulifera (LAMARCK, 1822) às variações ambientais previstas para manguezais estuarinos no Ceará - David, Heleny Noronha (2019)
Littoraria angulifera (Gastropoda: Littorinidae) is a mangrove gastropod that has the potential to function as an ecological indicator, since it can respond to environmental conditions through changes in the shape or size of its shell. Some animal species have been used as bioindicators of climate change, however, most of the studies carried out in recent years have used organisms belonging to terrestrial ecosystems. The objective of this research is to evaluate the effects caused by climate changes on Brazilian estuarine ecosystems, using L. angulifera as a bioindicator. For the purpose of this study, the sampling data from 2012 until the first semester of 2018 were used in Acaraú, Ceará, and each period was replicated twice, in low tides, at the end of the dry and rainy seasons. Three sites were selected in the vegetated habitat delimited by a contiguous region of 40m x 50m, where each sampling site has a distance of approximately 100m between them. A total of 50 individuals of varying sizes were collected manually from the trees at each site, at a maximum height of 1.30 m from the soil. Air, water and soil temperatures, relative air humidity, water salinity and rainfall were recorded at each sampling. In laboratory, measurements were made of height and width of the shell and weighing of the organisms (wet weight). The biometric data and the environmental variables collected in Acaraú, Ceará, were compared temporally. In addition, to test the effects of the temperature on the gastropods, a laboratory experiment was conducted to simulate the two scenarios of climate change predicted by the Intergovernmental Panel on Climate Change (IPCC), considering ambient temperature increases between 32ºC - 34ºC and 35 ° C-37 ° C. The height, width and weight of the shell correlated positively and significantly with rainfall, indicating that with the higher incidence of rainfall, the litorinids tend to have larger and heavier shells. In the experimental setting, the individuals of L. angulifera presented high mortality both in the Optimistic Scenario simulation and in the Pessimistic Scenario. The animals also presented different thermoregulatory behaviors in response to the temperature. When submitted to thermal elevation, in both scenarios, the organisms shifted down from leaves and branches or were concentrated closer to the base of the aquarium where the humidity was higher. These behaviors can be described as "Thermal Refuge Selection", which together with "foot retraction" were the main thermoregulatory behaviors which was observed in this specie during the experiment. According to the results presented, it is concluded that L. angulifera is a good indicator of environmental changes, since the size of its shell changes as a result of the environmental conditions and the animals were sensitive to the temperature increase predicted by the IPCC (2013), since there was a high mortality and incidence of thermoregulatory behaviors.